2013
DOI: 10.1614/ws-d-12-00130.1
|View full text |Cite
|
Sign up to set email alerts
|

Soil Microbial Root Colonization of Glyphosate-Treated Giant Ragweed (Ambrosia trifida), Horseweed (Conyza canadensis), and Common Lambsquarters (Chenopodium album) Biotypes

Abstract: Root colonization by soil microorganisms has been shown to increase the activity of glyphosate in resistant and susceptible biotypes of giant ragweed and a susceptible common lambsquarters biotype, but not in horseweed biotypes. The objective of this study was to investigate the colonization of roots in glyphosate-resistant and -susceptible giant ragweed and horseweed biotypes, and glyphosate-tolerant and -susceptible biotypes of common lambsquarters after a sublethal glyphosate application. The three weed spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…By using traditional culturing techniques, Pythium spp. were frequently isolated directly from the root tissue of glyphosate-treated GS giant ragweed; therefore this root-invading pathogen was proposed to play a role in glyphosate efficacy, and possibly glyphosate resistance (Schafer et al 2013). We anticipated that the molecular techniques used here would allow us to evaluate interactions among GS and GR giant ragweed biotypes to gain a deeper understanding of the role of the rhizosphere microbial community in the mode of action of glyphosate and glyphosate resistance.…”
Section: Alpha Diversity Indexmentioning
confidence: 99%
See 2 more Smart Citations
“…By using traditional culturing techniques, Pythium spp. were frequently isolated directly from the root tissue of glyphosate-treated GS giant ragweed; therefore this root-invading pathogen was proposed to play a role in glyphosate efficacy, and possibly glyphosate resistance (Schafer et al 2013). We anticipated that the molecular techniques used here would allow us to evaluate interactions among GS and GR giant ragweed biotypes to gain a deeper understanding of the role of the rhizosphere microbial community in the mode of action of glyphosate and glyphosate resistance.…”
Section: Alpha Diversity Indexmentioning
confidence: 99%
“…We cannot, however, highlight any perturbations that stand out as likely contributors to the herbicide-disease response observed in the plant. The microbial sequencing techniques used did not show that the soil-borne plant pathogen Pythium spp., typically implicated in this pathosystem with the use of classical techniques (Schafer et al 2013), were affected in the rhizosphere microbial community. We note, however, that in our previous studies Pythium spp.…”
Section: Alpha Diversity Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Root growth was not evaluated in our research, as it was by Alcorta et al (2011), who found that root mass was more than twofold greater for glyphosate-resistant than -susceptible horseweed. Furthermore, microbial communities in the rhizosphere have been shown to play a role in the differential response of glyphosate-resistant andsusceptible giant ragweed to glyphosate (Schafer et al 2012(Schafer et al , 2013. Schafer et al (2013) found that a glyphosate-resistant giant ragweed biotype from Indiana may be capable of withstanding soil microbial colonization, specifically oomycete colonization (predominantly Pythium spp.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, microbial communities in the rhizosphere have been shown to play a role in the differential response of glyphosate-resistant andsusceptible giant ragweed to glyphosate (Schafer et al 2012(Schafer et al , 2013. Schafer et al (2013) found that a glyphosate-resistant giant ragweed biotype from Indiana may be capable of withstanding soil microbial colonization, specifically oomycete colonization (predominantly Pythium spp. ), or that the defense mechanism of the roots may not be suppressed greatly by glyphosate compared to a glyphosatesusceptible biotype.…”
Section: Resultsmentioning
confidence: 99%